Women in Revolutionary Paris, 1789-1795 - Levy, Darline Gay; Applewhite, Harriet Branson; Johnson, Mary Durham (University of Illinois Press, 1979)
"Almost 200 years ago, the women of revolutionary Paris were demanding legal equity in marriage; educational opportunities for girls, including vocational training ; public instruction, licensing, and support for midwives; guarantees for women's rights to employment; and an end to the exclusion of women from certain professions. The editors have uncovered, translated, and annotated sixty documents which shed light on these and other socioeconomic struggles by women and their impact on the French Revolutionary era. This work makes a significant contribution to the growing appreciation of the role of women in history, politics, ideology, and social change."--Back cover.
Keywords: France; History; Paris; Political activity; Revolution, 1789-1799; Sources; Sources; France; Sources; Women; Women's rights; dept.psc; faculty_collection

Revolt in Athens; the Greek Communist "Second Round," 1944-1945, - Iatrides, John O. (Princeton legacy library, 1972)
Keywords: 1935-1967; Greece; Greece; Kommounistiko Komma Helladas; World War, 1939-1945; Politics and government; Underground movements; dept.psc; faculty_collection

Political Legitimacy in Revolutionary France, 1788-1791 - Applewhite, Harriet B. (The Journal of Interdisciplinary History, 1978)
Keywords: dept.psc

Book Review: Laird archer. balkan tragedy. manhattan, kansas: kansas state university, 1977. iv, 751 pp. 20.00 (published in conjunction with military affairs) - Iatrides, Johno (Canadian-american Slavic Studies, 1979)
Keywords: book.review; dept.psc

Sponsorship of Draft Resolutions and Amendments in Un-General-Assembly, 1946-1970 - Rai, KB (Polity, 1977)
Keywords: dept.psc

Political science in poland - Bodnar, Artur; Best, Paul J (PS Political Science & Politics, 1976)
Keywords: dept.psc

From liberation to civil war: the united states and greece, 1944-46 - Iatrides, John O (Southeastern Europe, 1976)
Keywords: dept.psc

Book Review: Mathematical applications in political science, VII . edited by james f. herndon and joseph l. bernd. (charlottesville: the university press of virginia, 1974. pp. 84. 9.75.) - Rai, Kul B (American Political Science Review, 1976)
Keywords: book.review; dept.psc

Lijphart's IA and pearson's r for studying un voting - Rai, Kul B (Comparative Political Studies, 1974)
Keywords: dept.psc

Foreign policy and voting in the UN general assembly - Rai, Kul B (International Organization, 1972)
Keywords: dept.psc